2009
DOI: 10.1016/j.surneu.2008.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Five-year follow-up of unilateral posteroventral pallidotomy in Parkinson's disease

Abstract: Background-Neurocognitive outcome research of individuals with Parkinson's disease following unilateral pallidotomy is inconsistent. While some studies reported few cognitive changes, other investigations have more consistently shown both transient and long-term cognitive decline postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 45 publications
1
15
0
3
Order By: Relevance
“…At 5 years after unilateral pallidotomy, motor UPDRS improved by 19% to 27%,41, 42 overall disability in the On‐medication condition (S & E scores) was stable,41 and ADL in the Off‐medication state improved 42. Mean tremor reduction was 65% after 4 to 5 years,41 and, if initially controlled by surgery, contralateral tremor remained improved up to 10 years 40.…”
Section: Long‐term Evolution Of Pd In Patients Treated With Lesionsmentioning
confidence: 96%
See 1 more Smart Citation
“…At 5 years after unilateral pallidotomy, motor UPDRS improved by 19% to 27%,41, 42 overall disability in the On‐medication condition (S & E scores) was stable,41 and ADL in the Off‐medication state improved 42. Mean tremor reduction was 65% after 4 to 5 years,41 and, if initially controlled by surgery, contralateral tremor remained improved up to 10 years 40.…”
Section: Long‐term Evolution Of Pd In Patients Treated With Lesionsmentioning
confidence: 96%
“…Cognitive decline was reported after 542 and 10 years of disease evolution,40 whereas LEDD increased in all patients who were followed for up to 10 years, without recurrence or induction of dyskinesia contralateral to pallidotomy 40. Severity of dyskinesia contralateral to pallidotomy diminished by 70% to 75% (UPDRS‐IV subscores)41, 42 after 5 years. Moreover, in a small subgroup of patients followed for up to 12 years, there was a tendency toward a sustained improvement in dyskinesia, although other parkinsonian signs did not improve 43…”
Section: Long‐term Evolution Of Pd In Patients Treated With Lesionsmentioning
confidence: 97%
“…Both segments of the globus pallidus, internal and external (Crossman, 1990;Obeso et al, 2008;Strutt et al, 2009) are overactive in animal models of L-DOPA-induced dyskinesia, and likewise in dyskinetic PD patients. The rodent equivalent of the primate external globus pallidus is the lateral pallidum (Maurice et al, 1997).…”
Section: Regional Distribution Of the Glial-inflammatory Markersmentioning
confidence: 99%
“…Pallidotomy has a prolonged effect on contralateral dyskinesia with previous studies having reported benefit lasting up to 13.5 years even when akinesia and other PD symptoms had returned 5. Other studies have also reported sustained benefit from unilateral pallidotomy on contralateral dyskinesia 1, 8, 9. None of these studies evaluated LID in a blinded fashion.…”
Section: Discussionmentioning
confidence: 98%